2014
DOI: 10.1002/adhm.201300676
|View full text |Cite
|
Sign up to set email alerts
|

Planar Microdevices for Enhanced In Vivo Retention and Oral Bioavailability of Poorly Permeable Drugs

Abstract: The development of novel oral drug delivery platforms for administering therapeutics in a safe and effective manner through the harsh gastrointestinal environment is of great importance. Here, the use of engineered thin planar poly(methyl methacrylate) (PMMA) microdevices is tested to enhance oral bioavailability of acyclovir, a poorly permeable drug. Acyclovir is loaded into the unidirectional drug releasing microdevice reservoirs using a drug entrapping photocross-linkable hydrogel matrix. An increase in acy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 40 publications
2
85
0
Order By: Relevance
“…When loaded with the model drug fluorescein and added to a Caco-2 monolayer under flow conditions, these devices increased permeation of drug 10-fold over that of a bolus dose [55]. Furthermore, Chirra et al demonstrated the effect of planar device geometry on adhesion in vivo [53]. When PMMA microdevices 200 μm in diameter and 8 μm in thickness (Figure 3 A) were administered to mice, they showed 27% retention in the proximal small intestine after 2 hours while PMMA microspheres of similar surface area demonstrated 12% retention.…”
Section: Strategies To Increase Micro/nanofabricated Oral Drug Delmentioning
confidence: 99%
“…When loaded with the model drug fluorescein and added to a Caco-2 monolayer under flow conditions, these devices increased permeation of drug 10-fold over that of a bolus dose [55]. Furthermore, Chirra et al demonstrated the effect of planar device geometry on adhesion in vivo [53]. When PMMA microdevices 200 μm in diameter and 8 μm in thickness (Figure 3 A) were administered to mice, they showed 27% retention in the proximal small intestine after 2 hours while PMMA microspheres of similar surface area demonstrated 12% retention.…”
Section: Strategies To Increase Micro/nanofabricated Oral Drug Delmentioning
confidence: 99%
“…These dimensions ensure that the microwells are small enough to have a good contact with the intestinal wall, but they are too large to be prone to endocytosis. In the literature, it has been reported when testing microdevices with similar dimensions on Caco-2 cells that an interaction between the microdevices and the in vitro intestinal cell line was found (Chirra et al 2014). Furthermore, it has been shown that microdevices with a similar diameter can stabilize amorphous forms of drug and avoid recrystallization as seen for amorphous forms without any confinement (Nielsen et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…4,5 For example, Desai et al have shown in the past years, that microfabricated containers are an oral DDS that can potentially increase the bioavailability of the loaded drug. 6,7 The first of these microfabricated DDS were produced in conventional materials such as Si, poly(methyl methacrylate) (PMMA) and photoresists. [8][9][10] In the last years, there have been efforts to fabricate such oral drug delivery microdevices in biocompatible and biodegradable polymers like poly-l-lactic acid (PLLA), polycaprolactone (PCL), poly(lactic-co-glycolic acid) (PLGA) approved by the US Food and Drug Administration (FDA) for applications in oral drug delivery.…”
Section: Hot Punching Of High-aspect-ratio 3d Polymeric Microstructurmentioning
confidence: 99%